1996
DOI: 10.1017/s1357729800015381
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cross, slaughter weight and halothane genotype on leanness and meat and fat quality in pig carcasses

Abstract: Carcass and meat quality traits were studied in 94 barrows of known HAL-1843 genotype (homozygote - - and heterozygote - +) from three crosses slaughtered at 90 kg and 120 kg live weight. Crosses A and B were produced from sires of which 0·5 of the genes were from a heavy-muscled × Large White line and 0·5 from pure Pietrain (A) or Duroc (B). Sows for both A and B were from a hyperprolific Large White × Landrace line and this latter line produced the pigs for cross C (control). The carcasses from cross A which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
23
7
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 18 publications
21
23
7
1
Order By: Relevance
“…In this experiment, meat redness (a*) increased and meat lightness (L*) and hue angle (H8) decreased as SW increased from 106 to 122 kg BW in accordance with most studies that report that meat becomes darker and redder (Latorre et al, 2004;Corino et al, 2009) and had more myoglobin content (García-Macías et al, 1996) as the pig ages. Meat from pigs slaughtered at heavier weight had more IMF and less moisture content than meat from pigs slaughtered at lighter weight in accordance with data of Candek-Potokar et al (1998b), Weatherup et al (1998) and (Corino et al, 2009).…”
Section: Carcass Traitssupporting
confidence: 91%
“…In this experiment, meat redness (a*) increased and meat lightness (L*) and hue angle (H8) decreased as SW increased from 106 to 122 kg BW in accordance with most studies that report that meat becomes darker and redder (Latorre et al, 2004;Corino et al, 2009) and had more myoglobin content (García-Macías et al, 1996) as the pig ages. Meat from pigs slaughtered at heavier weight had more IMF and less moisture content than meat from pigs slaughtered at lighter weight in accordance with data of Candek-Potokar et al (1998b), Weatherup et al (1998) and (Corino et al, 2009).…”
Section: Carcass Traitssupporting
confidence: 91%
“…Most authors have not detected any effect of breed on meat colour as measured by visual scores (Ellis et al, 1996), objective parameters (L*, a* and b*; Nieuwhof et al, 1991) or myoglobin content (García-Macías et al, 1996). However, loins from DU crossbreed had more lightness but were paler than those from PI crossbreed, in agreement with Latorre et al (2003a) who found higher a* values in loin from PI 3 LW than in that from DU-sired pigs.…”
Section: Meat Quality Traitsmentioning
confidence: 53%
“…Traditionally, PI pigs have shown consistently higher ham yield than DU pigs (Oliver et al, 1993). However, García-Macías et al (1996) observed that the proportion of lean cuts was similar between both breeds and Latorre et al (2003a and2003b) found that lean cut yield was higher for DU than for PI 3 LW offspring. Our results indicate that DU boars had a higher percentage of trimmed lean cuts than PI boars, and the difference was mostly due to the greater proportion of hams and shoulders.…”
mentioning
confidence: 99%
“…Weatherup et al (1998) observed that pork colour as measured by objective parameters was independent of slaughter weight. Garcia-Macias et al (1996), however, reported that increasing the body weight of the pigs to 133 kg caused higher myoglobin deposition with consequent redder meat. Age and slaughter weight had significant effect on texture property of pork L. dorsi, however, sex did not have any effect.…”
Section: Methodsmentioning
confidence: 97%
“…Leach et al (1996), however, observed more intramuscular lipid in muscles of barrows than gilts. Garcia-Macias et al (1996) reported that chemical composition of L. dorsi muscle was not affected by slaughter weight. the fat of the back region excluding the skin was measured at 1 st rib, last rib and last lumbar vertebrae.…”
Section: Methodsmentioning
confidence: 99%